Elite Political Behavior to Get Government Positions through Site Visits in Malang Regency - Fiqri Fadilah, Muhammad; Saiman, Saiman (Jurnal Sosiologi Agama, 2024)
The study discusses the behaviour of elites performing pre-election political rituals. This behaviour was carried out in the sacred place in Malang Regency. Political traditions contain the belief that symbols followed by elites interpret religion and politics. In this case, the elite who follow the election is closely related to the various contests that are contested. The study uses a qualitative descriptive approach with databases sourced from informants in the field through the interview process and separating vital and additional informants. It was discovered that the elite’s practice of political rituals was formed by a series of processions at the site of kingdom relics. Political patterns attached to the elite have turned into a form of tradition from initially just a pilgrimage process. This form of ritual is divided into stages. First, understand the ritual conditions and symbols. Second, interpret the patterns performed. Third, transform patterns in the actions of the political elite. This paper shows that studying political culture sourced from the elite still needs to be explored as a social phenomenon ahead of elections in Indonesia.